The utilisation of the GIS and GPS systems in creating acoustical databases for the outer environment - Kompała, J. (Archives of Acoustics, 2002)
In the paper, the usability has been characterised of recent computer-based GIG and GPS techniques related to charging the environment with vibroacoustical hazards. These techniques, joining the computer maps of the area with extensive databases, provide new research and application possibilities in investigating the propagation of noise and mechanical vibration in the environment and are a valuable tool in the so-called environmental management.